Implementasi Sistem Informasi Media Promosi Pada Semesta Resto Berbasis Website - Rudi Efendi, Muhammad; Yohana Tri Widayati; Satrio Agung Prakoso (Masyarakat Ekonomi Syariah Bogor, 2025)
This study focuses on the design and implementation of a web-based promotional media information system for Semesta Resto, a culinary business. The aim is to enhance the restaurant's operational efficiency and promotional effectiveness through a responsive website that offers interactive menus, online reservations, and real-time promotional updates. The research highlights the growing importance of digital media in the culinary industry, where consumer behavior is shifting towards online platforms. The study employs a qualitative descriptive approach, utilizing a case study methodology, and applies the Prototyping method in the development of the system. The findings demonstrate that the proposed system is expected to improve customer engagement, streamline operations, and increase revenue through better promotional strategies and easier customer interaction.